A Literature Review of Men-Centered Articles in the Adult Education Research Conference Proceedings 1997-2022 - Lisa Baumgartner (Adult Education Research Conference, 2024)
Abstract: I reviewed men-centered articles in the Adult Education Research Conference Proceedings between 1997-2022 to learn how men were portrayed and how hegemonic masculinity was demonstrated.
Keywords: men; hegemonic masculinity; literature review; adult education